PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SD NEGERI 157 PEKANBARU - Fitri Devanni; Hendri Marhadi; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This study in the background backs by its low learning outcomes IPA elementary school fourth grade students 003 Lubuk Sakat Kampar district. This is evidenced from 30 students only 14 students (46,66%) were scored according minimum completeness criteria (KKM) and 16 students (53,33%) whose grades do not correspond KKM of the first semester axam results while school set KKM is 65 with an average value of 60,50. This research is classrom action research (PTK) conducted aims to improve learning outcomes IPA elementary school fourth grade students 003 Lubuk Sakat Kampar district to implement cooperative learning model Think Pair Share (TPS). The research was conducted on 17 March 2015 through 01 April 2015 by two cycles. The subjects were fourth grade students 003 Lubuk Sakat Kampar district totaling 30 people who used the data source. Data collection instrument in this thesis is the teacher and students activity sheets as well as the achievement test. This thesis presents the results of learning derived from the value of daily test before treatment with an average of 60,50, cycle one rise on the average being 72,50. In the second cycle increased by an average of 76,83. The activities of teachers in the learning process in the first cycle of the first meeting and the second meeting 66,67%, 75% second cycle of the first meeting and the second meeting of the 87,50% increase to 91,67%. Results of the data analysis activity of students in the first cycle of the first meeting of 66,67% in the second meeting increased 70,83%. At the first meeting of the second cycle of 91,67% and in the second meeting increased to 95,83%. Research results in the fourth grade elementary school 003 lubuk sakat kampar district proves that the implementation of cooperative learning model Think Pair Share (TPS) can improve learning outcomes IPA.Keyword :outcome IPA, Model Think Pair Share